Different perspectives in measuring processes in psychodynamic child psychotherapy. Issue 1 (2nd January 2019) - Odhammar, Fredrik; Goodman, Geoff; Carlberg, Gunnar
ABSTRACT: The aim of this study was to explore how different measurements can contribute to understanding processes of change in psychodynamic child psychotherapy. The Child Psychotherapy Q-Set (CPQ) was compared with the child psychotherapist's description of the psychotherapy process, systematically collected every three months during therapy, and with the Feeling Word Checklist-24 (FWC-24) completed after each session. The aim was also to examine how these three different measurements together could describe change over time and how they were mirrored in the relationship between child and psychotherapist. The following questions were formulated: (1) What interaction structures can be identified with the CPQ? (2) How does the therapist describe the process in psychotherapy and how do therapists' feelings appear using the FWC-24? (3) How do the different measurements enrich one another and contribute to the understanding of the psychotherapeutic process? (4) How can the therapy be described compared to a hypothetical psychodynamic child psychotherapy prototype session? A videotaped child psychotherapy was analysed in its entirety. The CPQ provided a picture of the psychotherapist's and the child's actions and interactions, which complemented the subjective image of the psychotherapist when filling out questionnaires and the FWC-24. Analyses of the interaction between the child and the psychotherapist indicated the importance of creating a supportive and secure environment to achieve a feeling of psychological closeness, before working with the child's problems. The analysis of the therapy highlights the importance of the psychotherapist's meta-competence, i.e., overarching competencies that psychotherapists need to use to guide any intervention, what interventions to use, and when they are suitable.